Temporality in Qualitative Inquiry Theories, Methods and Practices - Clift, Bryan C.; Gore, Julie; Gustafsson, Stefanie; Bekker, Sheree; Costas Batlle, Ioannis; Hatchard, Jenny (Taylor & Francis, 2021)
social research & statistics; psychological methodology